PEMBUATAN WEBGIS ZONA NILAI TANAH UNTUK PENGHITUNGAN BPHTB SERTA PPH DALAM JUAL BELI TANAH DAN/ATAU BANGUNAN MENGGUNAKAN GOOGLE MAPS API (STUDI KASUS: KOTA SOLOK, PROVINSI SUMATERA BARAT) - Susanto, Yanto Budi; Zakkiyah, Wafa; Dediyono, Andy (Departemen Teknik Geomatika ITS, 2020)
Solok has a central role in supporting the economical sector of Solok’s citizens and Solok District in general. This role causes Solok City experience the increasing number of population every year. The increasing number of residents effects the increasing needs of houses that Tax Object Selling Value (called as NJOP) in Solok City. NJOP which is processed in such ways can be visualized into a map of land value zone. NJOP is used as the basis for determining the amount of tax value, one of which is the Fee for Acquisition of Land and Building Rights (called as BPHTB) and Income Tax (called as PPh) in the sale and purchase of land and/or buildings. This study aims to facilitate local governments in updating NJOP data which will be used in calculating BPHTB and PPh values and facilitating the public and PPAT / Notaries in knowing the BPHTB and PPh values that must be paid when buying or selling land and/or buildings. From this study it was found that WebGIS of land value zones that have been created can be used to calculate BPHTB and PPh, update NJOP data, and show tax calculation results in PDF form that are ready to be printed. The percentage of system feasibility for usability test is 80.38% with a proper predicate and conducting portability test by accessing webGIS zone of Solok City land value in ten web browsers and successfully ran.